The fourth slip of the flexor digitorum brevis muscle of the human foot. A systematic review and meta-analysis - Yammine, Kaissar (Italian Journal of Anatomy and Embryology, 2015)
The flexor digitorum brevis muscle, and in particular its fourth slip, has a significant clinical and surgical importance in medical practice. However, as for the majority of tendons destined to the little toe, the fourth slip is undergoing a phylogenetic degeneration. The aim of this meta-analysis is to conduct an evidence synthesis on the prevalence of FDB-5 and its variants in humans. Twenty-two studies met pre-defined inclusion criteria with a total of 2789 feet and 416 cadavers. Meta-analytical results of fourth slip agenesis were as follows; a) a true prevalence rate of 31.3%, b) a crude prevalence rate of 47%, c) a bilateral prevalence rate of 38.2%, d) a true prevalence rate of 77.3% in Indian populations, e) a true prevalence rate of ≈20% in Japanese, Chinese, American, European and Turkish populations, f) an Odds Ratio of 1.5 significantly in favor for female gender, g) non-significance for hand side, h) a true prevalence rate of a thin fourth slip of 47.7%, and i) a true prevalence rate of the variations of its origin in 12.3%. The knowledge of the frequency of  flexor digitorum brevis fourth slip agenesis and variations in relation to the demographic characteristics of patients would be of importance for tendon repair, tendon transfer or soft tissue reconstruction in foot surgery.